(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Plants are the sources of traditional medicine since time immemorial and several drugs that are currently used in clinics are of plant origin. Western Ghats of India, one of the hotspots in the world, comprises valuable medicinal plants and hardly a limited number of these have been scientifically validated. Thus, it is worth exploring the other medicinal plants from these regions. The information on ethnobotanical studies, indigenous and traditional knowledge on the medicinal plants from the Western Ghats of India were collected using online search engines such as Google, SCOPUS, Web of Science, Google Scholar, and PubMed. The collected information was analysed to understand the role of different plant species and families in treating various diseases and disorders using pharmacological approaches. It was found that around 1628 plant species belonging to 171 families were used for treating major ailments such as pain and inflammatory, gastrointestinal and, dermatological disorders. Furthermore, plant families including Fabaceae, Asteraceae and Acanthaceae were largely preferred. Amongst the reported species around 130 were endemic, 4 critically endangered and nearly threatened. Around 3 species were endangered and rare. One species is at risk. However, only 115 plants have been validated for their pharmacological properties using in vivo experiments and clinical trials/uses. The available literature on medicinal plants from the Western Ghats strongly suggests that these plants can be a potential source of the newer drug. Further in-depth studies on the screening of medicinal plants to isolate and characterize the pharmacologically important active principles are essential to contribute to the healthcare sector.